2022
DOI: 10.1177/08850666221102796
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Altered Gut Microbiota and Sepsis: A Hypothesis or an Authentic Fact?

Abstract: Sepsis, as an important public health concern, is one of the leading causes of death in hospitals around the world, accounting for 25% of all deaths. Nowadays, several factors contribute to the development of sepsis. The role of the gut microbiota and the response state of the aberrant immune system is dominant. The effect of the human microbiome on health is undeniable, and gut microbiota is even considered a body organ. It is now clear that the alteration in the normal balance of the microbiota (dysbiosis) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Thus, SCFA may have potential to attenuate exercise-associated epithelial perturbations, and subsequent systemic endotoxemia and/or bacteremia, which may flow onto reducing microbial translocation associated Ex-GIS incidence and severity (Gill et al, 2015a;Gill et al, 2015b;Gaskell et al, 2021b). Such protection may be attributed to enhanced epithelial cell (i.e., phospholipid bilayer) stability and/or tight-junction stability and regulation (Sekirov et al, 2010;Gilbert et al, 2018;Nabizadeh et al, 2022). There is evidence in human-exercise models to hypothesise that the presence of SCFA along the intestinal lumen, as a result of commensal microbial composition and function, may attenuate the effects of EIGS (Bennett et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SCFA may have potential to attenuate exercise-associated epithelial perturbations, and subsequent systemic endotoxemia and/or bacteremia, which may flow onto reducing microbial translocation associated Ex-GIS incidence and severity (Gill et al, 2015a;Gill et al, 2015b;Gaskell et al, 2021b). Such protection may be attributed to enhanced epithelial cell (i.e., phospholipid bilayer) stability and/or tight-junction stability and regulation (Sekirov et al, 2010;Gilbert et al, 2018;Nabizadeh et al, 2022). There is evidence in human-exercise models to hypothesise that the presence of SCFA along the intestinal lumen, as a result of commensal microbial composition and function, may attenuate the effects of EIGS (Bennett et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The growth chance of opportunistic bacterial pathogens increases in GM with dysbiosis conditions. Under normal conditions, the dynamic GM prevents pathogenic bacteria growth by producing antimicrobial agents and occupying receptors [ 4 ]. According to this evidence, and in agreement with other findings, in this study, pathogenic bacteria members of the Enterobacteriaceae and anaerobic Bacteroides sp.…”
Section: Discussionmentioning
confidence: 99%
“…Irregular responses to pro-inflammatory situations caused by infectious agents are considered the clear pathophysiology aspect of sepsis. Moreover, recent studies have shown that sepsis patients have a disorder in the body's homeostasis and suffer from suppressed cellular immunity in this condition [ 3 , 4 ]. On the other hand, in recent years, the link between gut microbiota (GM) and their metabolites, especially short-chain fatty acids (SCFAs), in the pathophysiology of sepsis has been highlighted [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemically, the microbial metabolites can displace past the intestinal epithelium via active or passive transport and directly affect the extra-intestinal tissues and cells [ 23 ]. Locally, metabolites produced by bacteria are sensed directly by the intestinal epithelial cells and affect the function of the gut epithelial barrier [ 24 , 25 ]. The lamina propria is a layer of loose connective tissue beneath the epithelial layer that its immune cells contribute to forming the mucosal immune system.…”
Section: Overview Of Microbiota Metabolitesmentioning
confidence: 99%